Potassium ions as a kinetic controller in ionic double layers for hysteresis-free perovskite solar cells. Issue 32 (31st July 2019) - Kim, Seul-Gi; Li, Cheng; Guerrero, Antonio; Yang, June-Mo; Zhong, Yu; Bisquert, Juan; Huettner, Sven; Park, Nam-Gyu
Abstract : This work highlights the clear correlation of ion migration and a fast generation of the double layer with severe hysteresis and long-term instability in perovskite solar cells and the importance of K + ions in reducing the kinetics affecting the ionic attachment to the contact surface. Abstract : Since ion migration and interaction with external contacts has been regarded as one of the origins for photocurrent density ( J )–voltage ( V ) hysteresis and phase segregation in perovskite solar cells (PSCs) under operational condition, control of ionic movement in organic–inorganic halide perovskites presents a big challenge for achieving hysteresis-free and stable PSCs. As a universal method, potassium doping into bulk perovskite films to minimize or eliminate the hysteresis was proposed. Here, we report direct observation of moderately retarded ion migration in K + -doped (FAPbI3 )0.875 (CsPbBr3 )0.125 perovskite by in situ photoluminescence (PL) imaging. However, more impressive is the effect on the kinetics for generation of the ionic double layer in the vicinity of the contacts as it is reduced by two orders of magnitude on the time scale when devices are doped with K + as detected by impedance spectroscopy. A significantly reduced hysteresis in the K + -doped perovskite is responsible for more prolonged stability exhibiting ∼96% of initial power conversion efficiency (PCE) after 22 days than relatively short-lived perovskites undoped with K + ions. This work highlights the clear correlation of ion migration and a fast generation of the double layer close to the contacts with severe hysteresis and long-term instability in PSCs and the importance of K + ions in reducing the kinetics affecting the ionic attachment to the contact surface.